DIFERENSIASI DALAM PEMBELAJARAN MATEMATIKA - Nurhaswinda; Nurhafizah; Alini Annisa Putri; Fitri Ayu Lestari; Salsabila (STKIP Subang, 2026)
This study aims to examine the application of differentiated learning in mathematics learning and analyze its impact on student learning processes and outcomes. The research method used was library research, reviewing various literature sources, including scientific journals and relevant previous research. The results of the study indicate that differentiated learning is an approach capable of accommodating diverse student characteristics, including readiness, interests, and learning profiles. The application of differentiation across content, process, product, and the learning environment has been shown to increase student engagement in mathematics learning. Furthermore, the results also indicate that differentiated learning has a positive impact on improving student learning outcomes, as indicated by increased learning activity, average grades, and percentage of learning completion. Learning becomes more effective, interactive, and meaningful because it is tailored to individual student needs. However, implementing this approach requires teacher readiness and competence in designing flexible and adaptive learning.